Biochemical characterization, structure-guided mutagenesis, and application of a recombinant D-allulose 3-epimerase from Christensenellaceae bacterium for the biocatalytic production of D-allulose - Guan, Lijun; Zhu, Ling; Wang, Kunlun; Gao, Yang; Li, Jialei; Yan, Song; Zhang, Xindi; Ji, Nina; Fan, Jing; Zhou, Ye; Yao, Xinmiao; Li, Bo (Frontiers in Bioengineering and Biotechnology, 2024)
D-Allulose has become a promising alternative sweetener due to its unique properties of low caloric content, moderate sweetness, and physiological effects. D-Allulose 3-epimerase (DAEase) is a promising enzyme for D-Allulose production. However, the low catalytic efficiency limited its large-scale industrial applications. To obtain a more effective biocatalyst, a putative DAEase from Christensenellaceae bacterium (CbDAE) was identified and characterized. The recombinant CbDAE exhibited optimum activity at pH 7.5 and 55°C, retaining more than 60% relative activity from 40 to 70 °C, and the catalytic activity could be significantly increased by Co 2+ supplementation. These enzymatic properties of purified CbDAE were compared with other DAEases. CbDAE was also found to possess desirable thermal stability at 55 °C with a half-life of 12.4 h. CbDAE performed the highest relative activity towards D-allulose and strong affinity for D-fructose but relatively low catalytic efficiency towards D-fructose. Based on the structure-guided design, the best doublemutation variant G36N/W112E was obtained which reached up to 4.21-fold enhancement of catalytic activity compared with wild-type (WT) CbDAE. The catalytic production of G36N/W112E with 500 g/L D-fructose was at a medium to a higher level among the DAEases in 3.5 h, reducing 40% catalytic reaction time compared to the WT CbDAE. In addition, the G36N/W112E variant was also applied in honey and apple juice for D-allulose conversion. Our research offers an extra biocatalyst for D-allulose production, and the comprehensive report of this enzyme makes it potentially interesting for industrial applications and will aid the development of industrial biocatalysts for Dallulose.